KENDALI PUTARAN MOTOR ASINKRON 3 PHASA DENGAN VSD TIPE ATV312HU15N4 - M. Suyanto; Subandi; Syafriudin; Arif Maulana Fikri (Fakultas Teknik, Universitas Muhammadiyah Prof. Dr. Hamka, Jakarta, 2019)
In the current industrial development, the use of 3 phase asynkron motors is widely used as a drive of equipment at full or relatively constant speed. The rotation arrangement of the asynkron motor is greatly influenced by the value of the frequency of the AC voltage entering the motor. This study discusses the problem of speed control of three phase induction motors using variable speed drive (VSD) type ATV312HU15N4, frequency 50 Hz, 2 HP. The right way to use electrical energy, for 3 phase asynchronous motor operations is to use VSD. VSD is a device consisting of a rectifier, inverter and controller. While the frequency setting aims to regulate the speed control of the 3 phase asynkron motor alternating current. Based on the results of testing in the laboratory found that the motor speed control using VSD, has a low starting current range (5.91-7.76A). While the load conditions and rotational speed range (313-1509rpm). This condition can be adjusted with changes in frequency, even if the load increases or decreases.